Retainable short-range order effects on the strength and toughness of NbMoTaW refractory high-entropy alloys. (November 2022) - Ji, Weiming; Wu, Mao See
Abstract: Short range order (SRO) can affect the dislocation glide and twin nucleation in high-entropy alloys (HEAs), leading to varying mechanical performance. However, the mechanical implications of SRO in refractory HEAs (RHEAs) remain largely unknown due to the lack of understanding of the nanoscale deformation. Here, the role of SRO on the tensile mechanical properties of single crystal equiatomic NbMoTaW RHEAs is investigated using the hybrid Monte Carlo method and molecular dynamics simulation. We find that the presence of SRO can simultaneously enhance the strength and toughness over a wide range of temperatures under very fast strain rate. The enhancement is larger at lower temperature due to higher degree of SRO. The effects of SRO strengthening and toughening are retainable after unloading from the plastic stage, due to the unexpected twinning-assisted pseudo-elastic deformation. The fundamental principles of SRO are provided to facilitate the rational design and applications of RHEAs. Graphical abstract: Image 1 Highlights: The presence of SRO breaks the strength-toughness trade-off of NbMoTaW. The SRO structures can recover after unloading from plastic deformation. SRO promotes the twinning-assisted pseudo-elastic deformation of NbMoTaW.